Ukuran Perusahaan Memoderasi Pengaruh Sensitivitas Industri Dan Profitabiltas Terhadap Pengungkapan Emisi Karbon - Maharani, Destin Alfianika; Arofah, Anastasia Anggarkusuma; Fatimah, Ika Siti; Latifah, Tiya (Institut Bisnis dan Informatika Kesatuan, 2022)
Disclosure of carbon emissions is a mechanism of concern and responsibility carried out by companies for the environment and the community around the industry. Disclosure of carbon emissions in Indonesia is included in the sustainability report and is still voluntary. However, the disclosure report can also be used as a form of support for the government in its efforts to reduce carbon emissions. The target of this study is to determine the effect of industry sensitivity and profitability on the disclosure of carbon emissions through company size. This research was conducted on non-financial public listed companies in the period 2019 – 2021. The data analysis technique used path analysis and hypothesis testing was carried out through a t test to empirically test the effect of industrial sensitivity and profitability on the disclosure of carbon emissions through firm size. The results of this study indicate that industry sensitivity and profitability have a positive and significant effect on firm size, industry sensitivity and profitability have a positive and insignificant effect on carbon emission disclosures, firm size has a positive and significant effect on carbon emission disclosures and firm size has a significant effect on sensitivity variables. industry and profitability on carbon emission disclosures.